Temperature-tunable lasing from dye-doped chiral microdroplets encapsulated in a thin polymeric film - Petriashvili, Gia; Bruno, Mauro Daniel Luigi; De Santo, Maria Penelope; Barberi, Riccardo (Beilstein Journal of Nanotechnology, 2018)
In the last decade, much interest has grown around the possibility to use liquid-crystal droplets as optical microcavities and lasers. In particular, 3D laser emission from dye-doped cholesteric liquid crystals confined inside microdroplets paves the way for many applications in the field of sensors or tunable photonics. Several techniques can be used to obtain small microresonators as, for example, dispersing a liquid crystal inside an immiscible isotropic fluid to create an emulsion. Recently, the possibility to obtain a thin free-standing film starting from an emulsion having a mixture of water and polyvinyl alcohol as isotropic matrix has been reported. After the water evaporation, a polymeric film in which the microdroplets are encapsulated has been obtained. Bragg-type laser emission has been recorded from the emulsion as well as from the thin film. Here, we report on the possibility to tune the laser emission as a function of temperature. Using a chiral dopant with temperature dependent solubility, the emitted laser wavelength can be tuned in a range of 40 nm by a temperature variation of 18 °C. The proposed device can have applications in the field of sensors and for the development of anti-counterfeiting labels.
Keywords: chiral microdroplets; dye-doped cholesteric liquid crystals; laser; polymeric films; temperature tuning